Entrepreneurial ecosystems: a holistic and dynamic approach - Claudia Shwetzer; Alex Maritz; Quan Nguyen (Journal of Industry-University Collaboration, 2019)
Purpose – The purpose of this paper is to add a holistic and dynamic approach to the emerging body of knowledge of entrepreneurial ecosystems (EEs). It aims to synthesise research and related neoteric EE concepts by proposing a conceptual framework for the study of the composition and interactions of such systems. Design/methodology/approach – The authors provide an emergent enquiry perspective by introducing a systematic literature review to inform the development of a conceptual framework, based upon theoretical underpinnings of institutional and network theory. Findings – This paper highlights neoteric holistic and dynamic approaches to recent scholarship of EEs, including antecedents, related concepts, shortcomings, features, actors, components and resources, recommendations for application, network and institutional perspectives, pathways for future research, and ultimately, a conceptual framework merging aspects of entrepreneurial activity, value creation, EE elements, relational interactions and institutional inferences. Research limitations/implications – Primary limitations are associated with holistic and dynamic approaches adopted in this study, highlighting that EE heterogeneity is unlikely conducive to a “one-size-fits-all” scenario; further empirical research on the dynamics of EEs is suggested to circumvent such implications while adding to the emerging and growing body of knowledge and application of EEs. Practical implications – The findings and conceptual framework provide a theoretical platform to base applications to practice in developing nascent and emerging EEs. Originality/value – A first of its kind study adds a holistic and dynamic emergent enquiry approach with institutional and network underpinnings to EE frameworks.